(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Misoprostol is very useful for induction of labour among the pregnant women. Objective: The purpose of the present study was to see the indication and complication of induction of labour by misoprostol among pregnancy women. Methodology: This single center clinical trial was carried out in the Department of Obstetrics and Gynaecology at a private hospital in Dhaka city, Bangladesh from September 2005 to February 2006 for a period of six months. Primi or second gravida patients with the gestational age between 37 weeks to 42 weeks in singleton pregnancy with cephalic presentation and not in labour were selected as study population. After proper selection of the cases, induction of labour was done by applying tablet misoprostol 50mcg in the posterior vaginal fornix. Complication of induction were recorded. Result: A total number of 60 patients were recruited for this study. 24 patients were between 23 to 26 years and 12 patients were between 27 to 30 years. Pre-eclampsia, pregnancy induced hypertension and intrauterine growth retardation were the most common indication of induction. In this study 31(51.7%) patients needed only 1 dose of Misoprostol and 24 (40.0%) patients needed 2 doses and only 5(8.3%) patients needed 3 doses of Misoprostal. In this study 11.67% patients experienced Nausea & vomiting and 3.33% patients developed hyperstimulation. Conclusion: In the conclusion, the use of misoprostol results in a shorter induction to delivery time and miserable adverse effects on the method of delivery. Journal of Current and Advance Medical Research 2020;7(2): 80-83